Elevation and vegetation determine Cryptosporidium oocyst shedding by yellow-bellied marmots (Marmota flaviventris) in the Sierra Nevada Mountains. Issue 2 (August 2015) - Montecino-Latorre, Diego; Li, Xunde; Xiao, Chengling; Atwill, Edward R.
Graphical Abstract